2015
DOI: 10.1016/s0924-9338(15)30379-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Relation Between Anxiety Disorders with Diabetic Type Two Patients's Quality of Life Reffering to Gorgan's 5th Azar Clinic of Diabetes in 2012

Abstract: Introduction and aimsDiabetes causes life expectancy reduction in to one third of optimal degree.several chronic complications are known for diabetes but psychiatric complications are rarely researched wherea diabetic patients have two times grater risk for mood disorders establishment than general population. So we aim to evaluate the anxiety disorders in diabetic type two patient's reffering to Gorgan's 5th Azar hospital clinic of diabetes in 1391 and then estimate their counter relations with their quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies [4,8,9,11,13] were carried out on diabetes "type I", adolescent diabetes, or diabetes of both types ' I ' and ' II '. The present study aimed at patients with diabetic mellitus ' type II '.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [4,8,9,11,13] were carried out on diabetes "type I", adolescent diabetes, or diabetes of both types ' I ' and ' II '. The present study aimed at patients with diabetic mellitus ' type II '.…”
Section: Discussionmentioning
confidence: 99%
“…As was mentioned earlier, diabetic patients get upset very easily and experience rapid changes in behavior. Studies have shown that anxiety disorders reduce the quality of life in patients with Diabetes Mellitus [8]. Therefore, both social and psychological aspects should be assessed as the main basis for the treatment of diabetes.…”
Section: Introductionmentioning
confidence: 99%